Comparison of the effects of perineural or intravenous dexamethasone on low volume interscalene brachial plexus block: a randomised equivalence trial. (January 2020) - McHardy, Paul G.; Singer, Oskar; Awad, Imad T.; Safa, Ben; Henry, Patrick D.G.; Kiss, Alex; Au, Shelly K.; Kaustov, Lilia; Choi, Stephen
Abstract: Background: Efforts to prolong interscalene block (ISB) analgesia include the use of local anaesthetic adjuvants such as dexamethasone. Previous work showing prolonged block duration suggests that both perineural and intravenous (i.v.) routes can both prolong analgesia. The superiority of either route is controversial given the design of previous studies. As perineural dexamethasone is an off-label use, anaesthesiologists should be fully informed of the clinical differences, if any, on block duration. This study was designed to test whether perineural vs i.v. dexamethasone administration are equivalent. Methods: We randomised 182 eligible patients scheduled for arthroscopic shoulder surgery to receive low-dose ISB (0.5% ropivacaine 5 ml) with perineural or i.v. dexamethasone 4 mg. Subjects, anaesthesiologists, and research personnel were blinded. All subjects also received a standardised general anaesthetic and multimodal analgesia. The primary outcome was duration of analgesia analysed as an equivalence outcome (2 h equivalency margin) using the two one-sided test (TOST) method. Results: For the primary outcome, duration of analgesia, and perineural and i.v. administration of dexamethasone were not equivalent. The upper and lower bounds of the 90% confidence interval were 1 h ( P =0.12) and –2.5 h ( P =0.01), respectively. The observed difference in mean block duration was not clinically relevant (0.75 h longer for i.v. dexamethasone). There were no other clinically significant differences between groups. Conclusion: In the context of low-volume ISB with ropivacaine, perineural and i.v. dexamethasone were not equivalent in terms of their effects on block duration. However, there were no clinically significant differences in outcomes, and there is no advantage of perineural over intravenous dexamethasone. www.clinicaltrials.gov registration: NCT02322242.